2008
DOI: 10.1002/ijc.23794
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of serum S100B in patients with cutaneous melanoma: A meta‐analysis

Abstract: S100B protein detected in the serum of patients with cutaneous melanoma has been long reported as a prognostic biomarker. However, no consensus exists on its implementation in the routine clinical setting. This study aimed to comprehensively and quantitatively summarize the evidence on the suitability of serum S100B to predict patients' survival. Twenty-two series enrolling 3393 patients with TNM stage I to IV cutaneous melanoma were reviewed. Standard meta-analysis methods were applied to evaluate the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 47 publications
4
82
1
8
Order By: Relevance
“…Unlike stage I-III, studies in stage IV melanoma patients displayed relevant heterogeneity. The meta-risk, however, was -independent of subgroup -always higher for S100B-positive patients [118], confirming a positive correlation between TNM stage and S100B-positivity. There is a significant rise in the percentage of S100B-positive patients when comparing various trials with patients at stage I-III (13.4 %), stage I-IV (28.3 %), and stage IV (41.8 %) alone (p < 0.0001).…”
Section: S100bmentioning
confidence: 55%
See 3 more Smart Citations
“…Unlike stage I-III, studies in stage IV melanoma patients displayed relevant heterogeneity. The meta-risk, however, was -independent of subgroup -always higher for S100B-positive patients [118], confirming a positive correlation between TNM stage and S100B-positivity. There is a significant rise in the percentage of S100B-positive patients when comparing various trials with patients at stage I-III (13.4 %), stage I-IV (28.3 %), and stage IV (41.8 %) alone (p < 0.0001).…”
Section: S100bmentioning
confidence: 55%
“…Technical parameters, e.g. an appropriate cut-off value, could not be identified in meta-analysis [118]. Separate evaluation of S100B at stage III was not conducted in this meta-analysis, in-stead combined assessment of stage I-III and I-IV.…”
Section: S100bmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful treatment with lymph node dissection, chemotherapy or immuno therapy was associated with decreased S-100B concentrations, whereas increased concentrations were an expression of disease progression [112,116,117]. Recently it was reported by several studies that S-100B can be used as a prognostic marker for disease-free survival and overall survival directly after therapeutic lymph node dissection in stage III melanoma [118][119][120][121]. Data from our center were not only in concordance with the above described findings, but also revealed that S-100B can be used as a prognostic marker for disease-free survival when determined before dissection.…”
Section: Reviewmentioning
confidence: 99%